Associação entre dor crônica e cognição de idosos cuidadores - Terassi, Mariélli (2015)
The caregiver who has the responsibility to take care of their elderly family member can modify their routine, increasing their workload and being susceptible to the appearance of pain. Chronic pain can interfere with the cognitive process leading to memory deficits, reduced time response, concentration and attention. Thus, this study aimed to evaluate the association between chronic pain and cognition in elderly caregivers. It is a descriptive, exploratory, with a quantitative approach and crosssectional design research. The study was conducted in Sao Carlos, a town in the state of Sao Paulo, Brazil, with sixty-year-old people or older who provide care to another elderly in the house. The final sample included 320 elderly caregivers, divided into two groups: one group with chronic pain (n = 187) and a group with no pain (n = 133). The instruments used for data collection were: sociodemographic characterization, health and care, Multidimensional Scale Evaluation of Pain (EMADOR), Addenbrooke´s Cognitive Examination - Revised (ACE-R), Inventory for Evaluation of overload, Perceived Stress Scale and Geriatric Depression Scale. The median age of the population was 68 years old, with a predominance of females (76.2%) and family income of three Brazilian median salaries. Regarding education, 17.5% (n = 56) were illiterate, 63.5% (n = 203) had one to four years at school, 9.4% (n = 30) five to nine years and 9, 6 (n = 31) ten years or more years at school. It was observed that the group with pain showed better level of education, with lower literacy rates when compared to the group without pain. In the group with chronic pain, 36.1% of the participants provide care for over 10 years and 26.9% spends 5-9 hours a day taking care of the elderly. In the group without pain, it was observed a lower percentage of participants who perform care for over 10 years. Caregivers with chronic pain had higher scores on overload scales, stress and depressive symptoms, with significant statistical difference between the groups. Regarding cognitive assessment, the elderly with chronic pain outperformed the elderly with no pain in all areas of the instrument ACE-R (Attention and orientation, memory, language, fluency and visuospatial skills). Regarding pain, 58.4% of seniors reported feeling pain for more than six months. The parts with the highest prevalence were the lumbar region (58.8%) and lower limbs (58.8%). There was a prevalence of moderate intensity (39.0%) and severe pain (38.6%). The descriptors listed by caregivers to represent pain were uncomfortable (92.5%), painful (87.1%) and sustained (73.7%). This study helped to identify the sociodemographic profile, health, care and characteristics of chronic pain of elderly caregivers attended at Public Health Units. It was not observed the association between chronic pain and worse cognitive performance, and caregivers with pain had better scores on the ACE-R than elderly people with no pain, showing a contrary result to the initial hypothesis, recommending the use of more specific instruments for future studies.